Pengaruh Bimbingan Belajar dari Orangtua dalam Peningkatan Prestasi Belajar Pada Siswa: Studi Kasus SMP Swasta YWKA Medan - Fildianti Fildianti (Cendikia : Media Jurnal Ilmiah Pendidikan, 2020)
Seeing the importance of how to educate parents in the family environment, the authors conducted a study with the aim to find out if there is a relationship in the way parents educate in the family environment with children's learning achievement in school. In this study, the authors determined a sample of 35 private junior high school students YWKA Medan who live with parents and both parents are still alive, through random sampling techniques. To collect data, closed questionnaires are used, to obtain data on how parents educate and documentary studies to obtain student learning achievement. Respondents' answers are given a value by giving a value weight for option a given a value of 4, for option b is given a value of 3, and for option c is given a value of 2, and for option d is given a value of 1. To find a correlation between the way parents educate and learning achievement is used pearson product moment formula as follows: Where: x is the value of the questionnaire, and y is the student's learning achievement. To test a hypothesis with a significant level of 5% or by using a belief level of 95% used a table r (correlation table) with a sample number of 35 people. Thus the result of the calculation obtained the value r = -0.08 and the value of r in the correlation table is 0.334. This means that there is a very low correlation. Thus it can be proven that the hypothesis in this study is rejected. So the author can conclude that the way parents educate is good can not improve students' learning achievement.